Anteseden Kinerja Operasional berdasarkan Sumber Daya Manusia dan Rantai Supplai - Kaluhuran, Anugrah; Sari, Nila Nova; Anggelina, Ria Rosita; Azizah, Tamara Zharifah; Masnita, Yolanda (Program Studi Manajemen, 2018)
The purpose of this research was to analyze between Human Resource, Supply Chain Outcomes, and Process Control Improvement with Operational Performance in the scope of company in Indonesia. The research was conducted using a quantitative approach and an online survey involving 250 employees at the manufacture company as samples. Sampling method is intentionally set according to research needs. Researchers used google form addressed to employees in any manufacture company. The analysis was carried out by multiple linear regression, which was previously pre-test and test for normality, validity and reliability with software IBM SPSS Statistic. Processing data using SEM with IBM SPSS Amos software tools. The results showed that Human Resource and Supply Chain Outcomes variable had a significant influence on Operational Performance. Then, together the Supply Chain Management Outcomes and Process Control and Improvement variables also have a significant influence on the Operational Performance.